Interactivity on Participatory Artworks. A Case Study of Long Life Laboratory - Rahardjo, Fransisca Retno Setyowati (Jurnal Multidisiplin Madani, 2024)
Contemporary art is a signifier for the occurance of the melting back aspect of melting back aspects of the arts with other non art disciplinesn in the art world as well as the creative industry. The collapse of hierarchies between high art and low art is the discourse in the West also influenced the development of art in Indonesia. This allows also many works popping up to a hybrid combination between pure art and design as applied art. Nowadays people believe the participatory art can be developed as the styled identity of Indonesia contemporary arts because of the collective spirit of commonly called ‘paguyuban’ it ussualy bring. There is a place called Jatiwangi Art Factory who developed an art movements by running a kind of community based methods to build their village out of economical bankruptcy. A similar approach was elaborated by a couple of Jakarta urban artist namely Irwan Ahmett and Tita Salina. They often work with the society in daily basis to criticize the Jakarta social problems. Departing from the above observation, this paper made to dissect the authos’s works entitled “Long Life Laboratory” which had been exhibited at the Bazaar Art Jakarta 2016 in Pacific Place Mall by measuring the level of interactivity on this kind work of participatory art. A Qualitative method is used also to read this visual form associated with the theory of relational aesthetic, a thinking of a French art critic Nicolas Bourriard